STRESS AND PSYCHOLOGICAL SUPPORT: MECHANISMS AND PSYCHOLOGICAL COPING STRATEGIES FOR PATIENTS WITH POSTTRAUMATIC DISORDERS - Boltivets, Sergii; Gonchar, Timur; Uralova, Lyudmila; Honchar, Oleksiy; Chelyadyn, Yuliya (Eastern Ukrainian Medical Journal, 2025)
Introduction. The relevance of this study stems from the widespread prevalence of neurotic disorders in contemporary society, driven by elevated stress levels, socio-economic instability, and other adverse factors. These disorders profoundly affect emotional well-being, diminish patients' quality of life and functional capacity, and impose a substantial strain on healthcare systems. Objective of the study was to analyze the mechanisms and efficacy of psychotherapeutic interventions for posttraumatic disorders. Methods. The methods employed included the State-Trait Anxiety Inventory, the Beck Depression Inventory, and the Short Form Health Survey. Descriptive statistics, Pearson correlation coefficients to assess the relationship between stress and symptoms, and regression analysis were utilized to evaluate the impact of interventions on symptom intensity and treatment effectiveness. Results. The results indicated significant reductions in anxiety and depression across all therapeutic interventions. Specifically, for cognitive behavioral therapy, the mean score on the State-Trait Anxiety Inventory decreased from 55 to 42 (t = 3.21, p = 0.003), while the mean score on the Beck Depression Inventory dropped from 25 to 12 (t = 4.23, p < 0.001). Conclusion. In the conclusions, the main findings of the study are summarized, emphasizing their importance for clinical practice and highlighting the necessity for further research. This research contributes to a new understanding of therapeutic psychological strategies for posttraumatic disorders, deepening insight and paving the way for evidence-based interventions in this field. Future research should explore the neural mechanisms of therapeutic change, the impact of social support, and the creation of culturally sensitive interventions.